2017
DOI: 10.1101/223206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Throughput Functional Evaluation of KCNQ1 Decrypts Variants of Unknown Significance

Abstract: Background -The explosive growth in known human gene variation presents enormous

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 39 publications
2
63
0
Order By: Relevance
“…Previous studies showed feasibility of this approach to study channel properties of K V 2.1 and the closely related K V 7.1 channel encoded by KCNQ1. 14,25,26 In addition, we also tested on this platform the T374I variant that we previously characterized by manual patch clamp recording, 7 and reproduced the loss-of-function phenotype (see Fig 2B; p < 0.001, unpaired t test @ +60mV vs WT). This further validates use of this platform to screen for K V 2.1 dysfunction.…”
Section: Consequences Of K V 21 Variants On Current Densitymentioning
confidence: 98%
“…Previous studies showed feasibility of this approach to study channel properties of K V 2.1 and the closely related K V 7.1 channel encoded by KCNQ1. 14,25,26 In addition, we also tested on this platform the T374I variant that we previously characterized by manual patch clamp recording, 7 and reproduced the loss-of-function phenotype (see Fig 2B; p < 0.001, unpaired t test @ +60mV vs WT). This further validates use of this platform to screen for K V 2.1 dysfunction.…”
Section: Consequences Of K V 21 Variants On Current Densitymentioning
confidence: 98%
“…Western blotting or confocal imaging, which are not scalable to thousands of variants. 17,43 Recent advances in automated patch clamp electrophysiology have enabled the rapid characterization of dozens of voltage-gated potassium channel variants, 31,44 and induced pluripotent stem cell derived cardiomyocytes show promise to characterizing KCNH2 variants in a non-heterologous system. However, the throughput of these methods does not allow for the rapid screening of the thousands of possible variants in KCNH2.…”
Section: Approaches To Studying Kcnh2 Variantsmentioning
confidence: 99%
“…While progress in the functional characterization of LQTS-associated mutations has been made (12)(13)(14) the mechanistic molecular basis of channel dysfunction for most KCNQ1 mutations is still unclear. The dearth of direct experimental data that can help to determine how mutations alter KCNQ1 structure and function has prompted computational modeling approaches (16,59).…”
Section: Rosetta-predicted Stability Changes In Kcnq1 Models Correlatmentioning
confidence: 99%
“…About 50% of the genetic cases of long QT syndrome (LQTS), which predispose children and young adults to sudden cardiac death, are associated with dominant mutations in KCNQ1 (type 1 LQTS) (11). While progress in the functional characterization of LQTS-associated mutations has been made (12)(13)(14)(15), the molecular mechanisms underlying channel dysfunction remain difficult to assess without the availability of high-accuracy structural data. A detailed molecular understanding is needed to improve decision making for new unclassified KCNQ1 mutations and to support the development of new anti-arrhythmic therapeutics.…”
Section: Introductionmentioning
confidence: 99%